Guide to load analysis for durability in vehicle engineering - Johannesson, Par; Speckert, Michael; Dressler, Klaus (Automotive series, 2014)
"Covers the use of established computational methods, such as finite element method (FEM) and multi body simulation (MBS), and their appropriate use within load analysis for durability"--